Effect of kinetics on the photocatalytic degradation of acetaminophen and the distribution of major intermediate with anatase-Ag synthesized by sol gel under visible irradiation - Aguilar, Claudia A.; de la Cruz, Alberto; Montalvo, Carlos; Ruiz-Marín, Alejandro; Oros-Ruiz, Socorro; Figueroa-Ramírez, Sandra J.; Abatal, Mohamed; Anguebes, Francisco; Córdova-Quiroz, Victor (Frontiers in Environmental Science, 2022)
The degradation of acetaminophen (ACET) was studied with TiO2-Ag catalysts, whose predominant crystalline phase was anatase, synthesized by the sol–gel method and doped by photo-deposition under UV radiation with silver particles. The catalyst was characterized by energy dispersive X-ray fluorescence (EDXRF) and X-ray diffraction (DRX). The acetaminophen degradation was determined by high-performance liquid chromatography (HPLC) and total organic carbon (TOC). The reaction behavior was studied under the Langmuir–Hinshelwood (LH-HW) equation and in a TOC-based model. With the experimental data, mass balances were performed to introduce the constants (reaction and adsorption kinetics) to the LH-HW equation. With the analysis of the generation and consumption behavior of the organic intermediate compounds (OI), coupled differential equations were generated, which express the degradation and formation-consumption behavior. The kinetic constants were obtained by nonlinear regression using the Levenberg–Marquardt equation. The results show high removal percentages, and the behavior of the experimental data is assumed to fit the LH-HW equation. The analysis of the organic intermediates by solid phase micro-extraction (SPE), HPLC and gas chromatography (CG-MS), shows that the transformation is feasible under the formation of nitro-aromatic derivatives and hydroxylated species.